Pelaksanaan Dual Sistem Pendidikan di Bawah Satu Naungan Pesantren Kecil (Studi pada MA dan SMA al-Falah Sumber Gayam Kadur Tahun 2016-2021) - M. Supardi (Magister’s Program in Islamic Education Postgraduate Program, Universitas Annuqayah Sumenep, 2022)
As an educational institution—mostly located in rural areas, Pesantren has initially carried out educational programs in the way know as sorogan and bandongan methods as the main methods. Recently, it developed into a classical model, formed into educational units that remained under the auspices of the Pesantren. The chosen education unit usually refers to the curriculum from the Ministry of Religious Affairs (Kementrian Agama) which is then called madrasah. The rapid development of education in fact requires some Pesantren to open new educational institutions affiliated with the Ministry of Education and Culture (Kemdikbud). It take these two ministries both similarities and differences to implement the curriculum. In addition, It is not merely a large Pesantren that implement education with a dual system model, but small pesantren either. Pesantren al-Falah and Sumber Gayam Kadur are such a small pesantren that implements education by that model. One of the educational institutions, included in the realm—dualism, are MTs and junior high schools, MA and SMA. This paper will go further to describe the management of educators and students in MA and SMA, including how is the relationship between MA and SMA? This research will come by the system theory and AGIL popularized by Talcots Parson assisted by comparative analysis to find its shortcomings and advantages. In the end, it was found that the implementation of dual education system under the auspices of one small pesantren has both positive and negative impacts. Various efforts are made to advance each educational institution, especially to attract limited human resources as the capital of the institution's sustainability. Therefore, efforts to attract students often lead to jealousy, controversy and opposition.